Potencial de genótipos de feijão-caupi para a produção de feijão verde no norte do estado do Ceará. - Almeida, Wener Santos de (2013)
The objective of this study was to evaluate the yield potential of cowpea genotypes for the production of green beans, and select the most appropriate to recommend to farmers how to cultivate the state of Ceará. We evaluated 16 genotypes of cowpea at Pentecost and Low Acaraú municipalities of Ceará. The experimental design was a randomized block with four replications. The variables evaluated were: green pod length, green pod mass, bulk grain green pod, number of pod green beans, green beans 100 mass index, green beans, yield of green pods and grain yield green. Was performed to correct moisture from green pods, being performed by the method of soaking water from beans and green beans until constant weight. Analyses of variance were combined and used to determine the genetic variability among the genotypes. Mean values for each variable were grouped by Scott-Knott. Correlations were estimated using path analysis following the model proposed by Li, determining the direct and indirect effects of yield components. Regarding the correction of moisture pods and green beans after harvest, it was observed that the original data have higher representativeness of the dry mass and require increased experimental precision, and correction of moisture from the pods of green beans and environmental conditions evaluated not necessary. With respect to yield and its components, we observed differential response of genotypes for all traits, indicating the presence of genetic variability. The BRS Tumucumaque genotype had the highest average grain yield components and green primary production in comparison with other genotypes at Pentecost. As for the municipality of Low Acaraú genotypes MNC05-841B-49 and Paulistinha had the highest average grain yield components and green primary production in comparison with other genotypes. Observed differential response of genotypes in the environments, indicating the necessity of performing path analysis for each situation. A selection of more productive genotypes in Low Acaraú should be done through indirect selection for grain yield component of green pod, since it presents greater direct effect on productivity, high heritability and high genetic variability coefficient and CVg / CVe greater than unity. Have a selection of more productive genotypes at Pentecost must be performed by indirect selection component yield of green pods, because this has high positive correlation with grain yield green.